2015
DOI: 10.4088/jcp.13m08790
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson’s Disease Following Zolpidem Use

Abstract: Zolpidem use might unmask preclinical Parkinson's disease, especially in patients with depression. However, large population-based, unbiased, randomized trials are warranted to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…To increase the validity of clinical diagnoses, PD cases were identified from patients diagnosed with Parkinson's disease (ICD-9-CM: 322) in at least three outpatient visits within one year or in a one-time hospital admission. This definition was also used in studies that utilized the NHIRD [ 42 , 43 ]. The control subjects were randomly selected from beneficiaries without PD using a matching strategy for age (±5 years), sex, the year of PD diagnosis and the year of NHI program entrance for each identified case.…”
Section: Methodsmentioning
confidence: 99%
“…To increase the validity of clinical diagnoses, PD cases were identified from patients diagnosed with Parkinson's disease (ICD-9-CM: 322) in at least three outpatient visits within one year or in a one-time hospital admission. This definition was also used in studies that utilized the NHIRD [ 42 , 43 ]. The control subjects were randomly selected from beneficiaries without PD using a matching strategy for age (±5 years), sex, the year of PD diagnosis and the year of NHI program entrance for each identified case.…”
Section: Methodsmentioning
confidence: 99%
“…The safety of a long-term treatment with zolpidem in patients with PD has been recently questioned by two recent retrospective observational studies, which analyzed a large Taiwan National Health Insurance database [ 74 , 75 ]. These studies suggested that the overall incidence of PD was significantly greater among a group of subjects with a history of assumption of zolpidem for more than 3 months as sleep-inducer, as compared to a group of subjects without a history of assumption of zolpidem [ 74 , 75 ].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…The safety of a long-term treatment with zolpidem in patients with PD has been recently questioned by two recent retrospective observational studies, which analyzed a large Taiwan National Health Insurance database [ 74 , 75 ]. These studies suggested that the overall incidence of PD was significantly greater among a group of subjects with a history of assumption of zolpidem for more than 3 months as sleep-inducer, as compared to a group of subjects without a history of assumption of zolpidem [ 74 , 75 ]. In the first study [ 74 ], the group of subjects who received zolpidem had a higher cumulative rate of PD than the group of subjects who did not receive zolpidem during a 5-year follow-up period, while in the second study [ 75 ] after 5 years of observation the incidence of PD did not differ between the two groups.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In addition, we have published related studies according to the same diagnoses and ICD-9 codes. 26 29 …”
Section: Methodsmentioning
confidence: 99%